Laser Interstitial Thermal Therapy for Mesial Temporal Lobe Epilepsy. (1st December 2016) - Wicks, Robert T.; Jermakowicz, Walter J.; Jagid, Jonathan R.; Couture, Daniel E.; Willie, Jon T.; Laxton, Adrian W.; Gross, Robert E.
Abstract: Approximately one-third of patients with epilepsy do not achieve adequate seizure control through medical management alone. Mesial temporal lobe epilepsy (MTLE) is one of the most common forms of medically refractory epilepsy referred for surgical management. Stereotactic laser amygdalohippocampotomy using magnetic resonance-guided laser interstitial thermal therapy (MRg-LITT) is an important emerging therapy for MTLE. Initial published reports support MRg-LITT as a less invasive surgical option with a shorter hospital stay and fewer neurocognitive side effects compared with craniotomy for anterior temporal lobectomy with amygdalohippocampectomy and selective amygdalohippocampectomy. We provide a historical overview of laser interstitial thermal therapy development and the technological advancements that led to the currently available commercial systems. Current applications of MRg-LITT for MTLE, reported outcomes, and technical issues of the surgical procedure are reviewed. Although initial reports indicate that stereotactic laser amygdalohippocampotomy may be a safe and effective therapy for medically refractory MTLE, further research is required to establish its long-term effectiveness and its cost/benefit profile.